Bimbingan Perkawinan dalam Perspektif Empirisme dan Maqashid Syariah - Moch Yusuf Syakir Pratama; Achmad Khudori Soleh (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Marriage guidance for teenagers of marriageable age can provide insight into entering a marriage. Therefore, marriage guidance regulated by the Ministry of Religion is important. This study aims to analyze marital guidance from empiricism and maqashid Sharia. The research method uses a literature review with a qualitative and comparative approach. The results showed that empirically marriage guidance is an activity needed by teenagers of marriageable age, so it is important to carry out. From the maqashid perspective, marriage guidance can benefit teenagers of marriageable age in fostering a sakinah family. The material is related to matters related to marriage, problems that often arise, and tips for fostering a Sakinah family.